A new genus of Nearctic oak gall wasp, Grahamstoneia Melika & Nicholls, gen. nov. (Hymenoptera: Cynipidae, Cynipini) - Melika, George; Nicholls, James A. (Zootaxa, 2021)
A new genus, Grahamstoneia Melika & Nicholls, gen. nov., with one new species, G. humboldti Melika & Nicholls, sp. nov., asexual generation, is described. This new taxon occurs in the south-western Nearctic, inducing galls on two species within Quercus section Protobalanus (Q. vacciniifolia Kellogg and Q. chrysolepis Liebm.), an ecology and distribution shared with the closely related genus Heteroecus Kinsey. Descriptions, diagnoses, biology, and host associations for the new genus and species are given. The new taxon is supported by morphological and molecular data.